Antimicrobial photodynamic inactivation as an alternative approach to inhibit the growth of Cronobacter sakazakii by fine-tuning the activity of CpxRA two-component system - Xu, Jinchun; Yao, Huangbing; Li, Yali; Liao, Qiaoming; Wan, Xiaoxiao; Liu, Lulu; Ma, Xiaojing; Tao, Han; Wang, Hui-Li; Xu, Yi (Frontiers in Microbiology, 2023)
Cronobacter sakazakii (C. sakazakii) is an opportunistic foodborne pathogen primarily found in powdered infant formula (PIF). To date, it remains challenging to control the growth of this ubiquitous bacterium. Herein, aPDI (antimicrobial photodynamic inactivation) was first employed to inactivate C. sakazakii. Through 460 nm light irradiation coupled with hypocrellin B, the survival rate of C. sakazakii was diminished by 3~4 log. The photokilling effect was mediated by the attenuated membrane integrity, as evidenced by PI staining. Besides, scanning electron microscopy showed the deformed and aggregated cell cluster, and intracellular ROS was augmented by 2~3 folds when light doses increase. In addition to planktonic cells, the biofilm formation of C. sakazakii was also affected, showing an OD590nm decline from 0.85 to 0.25. In terms of molecular aspects, a two-component system called CpxRA, along with their target genes, was deregulated during illumination. Using the knock-out strain of ΔCpxA, the bacterial viability was reduced by 2 log under aPDI, a wider gap than the wildtype strain. Based on the promoted expression of CpxR and OmpC, aPDI is likely to play its part through attenuating the function of CpxRA-OmpC pathway. Finally, the aPDI system was applied to PIF, and C. sakazakii was inactivated under various desiccated or heated storage conditions. Collectively, aPDI serves as an alternative approach to decontaminate C. sakazakii, providing a new strategy to reduce the health risks caused by this prevalent foodborne pathogen.